Greece's geopolitics of the aegean sea during the syriza-led government (2015-2019) - MERT UZUNER, ZUHAL (Nobel Yayın Dağıtım, 2020)
The governmental profiles of both Turkey and Greece have been discussed and referred to as important determinants of emerging policies. SYRIZA, as a Greek party of the radical left and progress, was considered very promising to challenge settled approaches in politics in Europe and this final manoeuvre can be seen as a symbol for that. So, is it possible to argue that SYRIZA followed a different path in the geopolitical orientations and the foreign policy of Greece? b) What was the standpoint of SYRIZA about Turkish-Greek relations and the geopolitical significance of the Aegean Sea? In any attempt to examine the geopolitical considerations of state governments, geopolitical terminology which is preferred or used in the discourses of state leaders or leading political figures shall be referred to carefully.This paper argues that the SYRIZA-led government’s geopolitical considerations show no serious change - compared to its predecessors - despite the left-ideological origins of SYRIZA, its critical stance and the contempt that SYRIΖΑ had for power politics in international relations or geopolitical analysis in the years before the elections of 2015, when it was a party of left opposition, activism and intensive critique.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uluslararası İlişkiler; Diğer; Social Sciences and Humanities; Political Science; International Relations; Other; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; ULUSLARARASI İLİŞKİLER; POLİTİKA BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INTERNATIONAL RELATIONS; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities